Basic concepts and definitions of the PAS design and decision system - Arkesteijn, Monique (A+BE | Architecture and the Built Environment, 2019)
In this chapter, using basic concepts and definitions from management science, decision theory and design methodology, I shall outline the methodological aspects, characteristics and features of the Preference-based Accommodation Strategy (PAS) design and decision system, which I developed for the formation of a corporate accommodation strategy. This outline serves first and foremost as a simple way of representing and modeling the PAS design decision system. It also enables the methodological characteristics of PAS design and decision making to be set out in a way that allows analysis and evaluation of the suitability of the applications of this system in real life corporate accommodation strategy processes. Finally, it should be possible to incorporate past experience into the framework, and to generalize and summarize it in order to benefit the further development of the PAS design decision system. The PAS design decision system will be referred to as PAS. In chapter 2 the existing alignment models were assessed on eight different assessment criteria and it has become clear that decision making receives very little attention in the models. The two main problems were that (1) it remained unclear how alternative CRE strategies are made on portfolio and building level and (2) most problems occur when selecting an alternative; none of the models has an overall performance measure that incorporates both quantitative and qualitative criteria, and uses correct measurement. Although in paragraph 2.2 all assessment criteria have been introduced, some of the concepts will be explained in this chapter. In chapter 2.3 the models have been assessed on their use of correct measurement for instance. In paragraph 3.2 it will be explained what correct measurement is and why it is important. The chapter is structured as follows: –– Fifteen basic concepts underlying the PAS design system are explained in paragraph 3.1; –– Preference measurement as core concept is explained in more detail in paragraph 3.2; –– Preference-Based Design as other core concept is explained in more detail in paragraph 3.3; –– A comparison of the foundations in different scientific field in given in paragraph 3.4; –– The chapter ends with a conclusion and comparison in paragraph 3.5.